2013
DOI: 10.1155/2013/917068
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-Related Hospitalizations following Prophylaxis in the Canadian Registry for Palivizumab (2005–2012) Compared to Other International Registries

Abstract: Respiratory syncytial virus (RSV) infection occurs commonly in infants aged ≤2 years, and severe infection results in hospitalization with accompanying morbidity and mortality. Palivizumab has been available for prophylaxis for the past 15 years. Prospective data on patients who received palivizumab from 2005 to 2012 has been assembled in the Canadian registry (CARESS) to document utilization, compliance, and health outcomes in both hospital and community settings. Long-term data is necessary to evaluate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
4
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 55 publications
4
24
4
4
Order By: Relevance
“…The number of immunized children constituted 0.5 % of the total number of children born alive at the UCH Mostar during the study period (approximately 14400). The results of research conducted in Canada over a 7-year period indicate that 10.6 % of patients immunized with palivizumab had CHD [14], which is a significantly smaller percentage of children with CHD in relation to our research. The immunization was administered in the neonatal dispensary, and the parents were informed of the event a few days earlier, which is, in part, an inappropriate way of offering services to children and their parents.…”
Section: Discussioncontrasting
confidence: 41%
“…The number of immunized children constituted 0.5 % of the total number of children born alive at the UCH Mostar during the study period (approximately 14400). The results of research conducted in Canada over a 7-year period indicate that 10.6 % of patients immunized with palivizumab had CHD [14], which is a significantly smaller percentage of children with CHD in relation to our research. The immunization was administered in the neonatal dispensary, and the parents were informed of the event a few days earlier, which is, in part, an inappropriate way of offering services to children and their parents.…”
Section: Discussioncontrasting
confidence: 41%
“…The prevalence of HS-CHD (22.6%) and of NMA/CAA (11.3%) were high in the present study compared with previous studies, while that of prematurity (gestational age <35 weeks, 8.1%) and of CLD (11.3%) were relatively low. 5,6,[19][20][21][22] These observations might be due to differences in PZ prophylaxis according to risk factors in different countries. [23][24][25] In a retrospective study of RSV-related re-admissions of preterm infants (gestational age <34 weeks) in South Korea, Lee et al reported that 47.5% of 1,140 preterm infants received PZ prophylaxis, including 89.3% of those with CLD.…”
Section: Discussionmentioning
confidence: 99%
“…Palivizumab-treated children with DS (n = 532) were selected from the Canadian RSV Evaluation Study of Palivizumab (CARESS [27][28][29] Children enrolled in the registry have received $1 dose of palivizumab and are followed for the respective annual RSV season. For this analysis, subjects were selected based on the documented presence of DS.…”
Section: Treatment Groupmentioning
confidence: 99%